UMPSA’s BVI and BVE graduates are in high demand by the Automotive and Electronics Industries - Naqiah, Puaad (UMPSA, 2024)
PUTRAJAYA, 25 August 2024 – Graduates from the Bachelor of Industrial Electronics Automation Technology (BVI) and Bachelor of Electrical System Maintenance Technology (BVE) programmes, offered by the Faculty of Electrical and Electronics Engineering Technology (FTKEE) at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), have become highly sought after by the automotive and electronics industries.